USING MULTIMEDIA INTERACTIVE GRAMMAR TO ENHANCE POSSESSIVE PRONOUNS AMONG YEAR 4 PUPILS - Yee Bee Choo; Vivian Kwon (Journal of English Education, 2017)
This study was designed to improve the students’ grammar specifically in possessive pronouns using Multimedia Interactive Grammar (MIG) as a teaching and learning strategy. The participants of the study were Year 4 pupils from a primary school and the researcher was the teacher who conducted the action research in the classroom and the cycle of the intervention had been done once. The data collected were tests, supported with interview and teacher’s reflective journal. Improvement was shown based on the data obtained as there was an increase of scores in the second test compared to first test. Moreover, it was found that MIG was able to enhance pupils’ understanding, motivation and promote fun learning in the classroom. The results of the study indicated pupils’ positive behaviors and responses towards the use of MIG in learning grammar.